Exploring the emission reduction and economic impacts of environmental regulation from a dynamic endogenous perspective: evidence based on the PVAR and threshold models - Zhaoqiang Zhong; Zhiguang Chen (Humanities & Social Sciences Communications)
Abstract How to effectively reduce pollution emissions and achieve high-quality economic development (HQED) is an important challenge currently facing China. On the basis of China’s provincial panel data from 2008 to 2020, this paper constructs a panel vector autoregression (PVAR) model, to clarify the dynamic interactive relationships among environmental regulation, pollution emissions and HQED from an endogenous perspective. On this basis, the threshold model was used to test the threshold effect of environmental regulation and pollution emission intensity. The results indicate the following: (1) A bidirectional Granger causality relationship exists between environmental regulation and pollution emission, and between pollution emission and HQED, with environmental regulation being a one-way Granger cause of HQED. (2) Environmental regulation can significantly promote HQED in the long term. Pollution emission intensity and HQED have a mutual inhibitory effect, with the inhibitory effect of pollution emission intensity showing a lag, and a long-term “inverted M” pattern. Pollution emission intensity has a positive promoting effect on environmental regulation intensity in the long term, whereas the reverse relationship is inhibitory, following an inverted U-shaped trend. (3) Variance decomposition reveals that, in addition to the variables themselves, pollution emissions contribute the most to the intensity of environmental regulation. Environmental regulation contributes the most to the other two variables. (4) The threshold regression model indicates that when the intensity of environmental regulation crosses the threshold value of 0.8430, pollution emission intensity has a significant negative impact on HQED. When pollution emission intensity crosses the second threshold value of 0.4870, the intensity of environmental regulation begins to show a positive promoting effect. This article not only effectively supplements the EKC hypothesis from a theoretical level, but also clarifies the dynamic interactive relationship between environmental regulation, pollution emissions and HQED from a practical level, providing a reference for the government to improve environmental regulation policies and facilitate HQED in China.